(untitled) (Research, Society and Development, 2025)
Leptospirosis is a globally relevant zoonosis with high incidence in the Brazilian Northeast, mainly due to environmental and socioeconomic factors associated with tropical climate and high rainfall. To describe the profile of students from public schools in the metropolitan region of Recife/Pernambuco and their knowledge about leptospirosis. This descriptive and exploratory study involved 201 students from public schools in Pernambuco, using questionnaires addressing sociodemographic, environmental data, and level of information about leptospirosis. Most participants identified as female (62.1%) and mixed-race (51.7%), aged 17 to 18 years (45.7%). Overall, 60.5% of students reported living in flood-prone areas, and only 19.1% stated familiarity with the topic. Knowledge about leptospirosis showed no statistically significant association with socioeconomic conditions or environmental exposure to flood risk areas. Despite some knowledge about leptospirosis, notable gaps remain regarding symptoms and preventive practices, reinforcing the need for effective educational actions. Thus, integrated education strategies and public policies are essential to mitigate the impacts of leptospirosis in Recife/PE.